Porcelain veneer for a simple and esthetic treatment on anterior teeth with enamel hypoplasia: a case report - Juni Jekti Nugroho; Andi Hermianti Aco (Conservative Dentistry Journal, 2019)
Introduction: the esthetic factor should be considered for every patient who seeks a comprehensive dental treatment, especially for women. The anterior teeth deformities will diminish the levels of confidence and decrease self-esteem of the patients. The tooth development disturbances, such as enamel hypoplasia, may present an esthetic problem. Enamel hypoplasia is an alteration of organic matrix formation which characterized by the defect or porosity on the enamel surface. It can be restored with a variety of restorative treatment options including indirect porcelain veneers. Case: a 30 years old female patient was referred with chief complaint of anterior teeth discoloration. Clinical examination on the maxillary left central and lateral incisors revealed the defects on nearly half of the labial surface. Case management: the incisal lapping technique were chosen to prepared teeth #21 and #22 for indirect porcelain veneer fabrications. Conclusion:  indirect porcelain veneers established an excellent esthetic result and restored the size, shape and color of anterior teeth with long term stability.